PEMBERDAYAAN WARGA NEGARA DALAM PELAYANAN PUBLIK MANAJEMEN PENDIDIKAN DASAR DI KOTA KENDARI - . Rahman (Universitas Bandar Lampung (UBL), 2016)
The purpose of this study is to analyze and describe the empowerment of citizens by local governments in the management of basic education. The method used in this study is a research method using a qualitative approach, a procedure that emphasizes research on the characteristics of natural background, the researcher as an instrument, while collecting data methods are deep interview, obsercation and documentations. The focus of research produces descriptive data in the form of the written and spoken word and analyzed inductively.The results showed that the Kendari municipal government has been trying to empower citizens by involving them in decision making related to the implementation of basic education management. Citizen empowerment is not optimal. Forms of citizen empowerment visible in activities (1) Regional Development Planning Meeting, (2) the School Committee, (3) The hearing in Parliament of Kendari and (4) Meeting at the Department of Education and Culture in Kendari City.